EFEKTIVITAS ASESMEN PROYEK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI DI SEKOLAH MENENGAH ATAS - Lussana Rossita Dewi; Amalia Gratiana; Ipah Budi Minarti (Universitas Cokroaminoto Palopo, 2022)
Project assessment is an assessment carried out by the teacher in observing the process of student activities. Project assessment requires students to complete project assignments using measuring tools and skills that are manifested in the form of actions, actions or work projects. This study used a Pre Experimental Design research design in the form of One Group Pretest-Posttest Design. Data collection techniques used in this study include: 1) non-test test techniques, consisting of: (a) direct observation and assessment of the project learning assessment tool design by validity; (b) direct observation and assessment of the implementation of the assessment instrument given to the observer; and (c) giving teacher response questionnaires to collect data on the feasibility of project learning assessments and 2) test technique, namely giving multiple choice item tests to students to determine students' understanding of the project activities that have been implemented. The results of this study indicate that there are differences in the learning outcomes of class XII students who receive Biology learning material on Plant Growth and Development with project assessment learning and those who do not. It is shown from the results of hypothesis testing the value of student learning outcomes, obtained a significance value (0.027 < 0.05).